2009
DOI: 10.2172/968186
|View full text |Cite
|
Sign up to set email alerts
|

Lifecycle Cost Analysis of Hydrogen Versus Other Technologies for Electrical Energy Storage

Abstract: online ordering: http://www.ntis.gov/ordering.htm Printed on paper containing at least 50% wastepaper, including 20% postconsumer waste iii Executive SummaryAs renewable electricity becomes a larger portion of the electricity generation mix, new strategies will be required to accommodate fluctuations in energy generation from these sources. One of the primary strategies proposed for integrating large amounts of renewable energy is using energy storage to absorb excess electricity-generating capacity during tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 8 publications
0
38
0
Order By: Relevance
“…Comparing to the other storage technologies that can also take advantage of performing energy arbitrage in a electricity spot market, the study performed in [35] showed that compressed air energy storage (CAES) and pumped hydro were the two winners. The comparison was performed based on a unified size of 300 MWh scale energy storage with a discharge rate of 50 MW, while using annualized cost for producing the energy output from the storage system as the metric: electricity fed back onto the grid during peak hours and, in the case of producing excess hydrogen for vehicles, hydrogen.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing to the other storage technologies that can also take advantage of performing energy arbitrage in a electricity spot market, the study performed in [35] showed that compressed air energy storage (CAES) and pumped hydro were the two winners. The comparison was performed based on a unified size of 300 MWh scale energy storage with a discharge rate of 50 MW, while using annualized cost for producing the energy output from the storage system as the metric: electricity fed back onto the grid during peak hours and, in the case of producing excess hydrogen for vehicles, hydrogen.…”
Section: Resultsmentioning
confidence: 99%
“…Polymer electrolyte membrane electrolysers [7] are being developed and are expected to have increased operational efficiencies and could potentially lower the overall costs of the electrolyser. Different efficiencies were stated for the compression of hydrogen ranging from low efficiencies of 52 % [8] to high efficiencies of 85 % [9].…”
Section: Hydrogen Storagementioning
confidence: 99%
“…The proton exchange membrane fuel cell (PEMFC) is the most advanced for transport and stationery applications and has an efficiency of 53.5 % [8]. Another fuel cell that is in the research phase is the solid oxide fuel cell [10] (SOFC) which is estimated to have higher efficiencies due to high operating temperatures in which some of the heat can be used to supply heat for domestic purposes.…”
Section: Hydrogen Storagementioning
confidence: 99%
See 1 more Smart Citation
“…This is an attractive energy storage system that combines several known subsystems into a complete system. NREL has reported on an analysis of hydrogen storage versus other electrical energy storage systems (Steward et al 2009). …”
Section: Hydrogenmentioning
confidence: 99%